Cryptocurrency Sebagai Mata Uang, Komoditas, dan Instrumen Investasi Dalam Perspektif Sad Dzariah - Astutik, Erni Dwi; Ghozali, Mohammad Lathoif (Fakultas Syariah INSURI Ponorogo, 2022)
In recent years, technological advances have grown so rapidly, including progress in the economic field. the existence of cryptocurrencies or digital money, provides a new alternative as a transaction tool, investment instrument or as a trading commodity. On the other hand, the legitimacy of using cryptocurrencies is still a matter of debate in various circles. Researchers want to study the use of cryptocurrencies with the sadd dzariah approach. This research is a quantitative research and is a library research. The data analysis technique used is descriptive-analytical with a normative juridical approach to Islamic law. The results of the study indicate that the use of cryptocurrencies in business transactions, as an investment instrument, and illegally traded commodities, is maysir and gharar. So it should be avoided containing mafsadat rather than benefit, and has the potential to bring more harm than good/mafsadah.